Advanced analytical methods for preventing scaling and ensuring water quality in bioenergy generation processes - Souza, Érik Geraldo da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This study addresses the challenges associated with bioelectricity generation in the sugar-energy industry, focusing on scaling formation and water quality management in the steam generation process. Utilizing water-tube boilers fueled by sugarcane bagasse and straw, these biorefineries produce high-pressure steam to drive turbines and generate electricity for both internal consumption and the national power grid. The thesis is structured into two chapters. The first chapter investigates scaling formation in turbogenerators, employing techniques such as energy-dispersive X-ray fluorescence (ED-XRF) and principal component analysis (PCA). Samples collected from critical points in the turbines and boilers revealed the predominant presence of elements such as silicon (Si), sulfur (S), chlorine (Cl), potassium (K), and calcium (Ca), which contribute to scaling formation. The results emphasize the direct relationship between water quality and scaling, highlighting the importance of rigorous water treatment controls to prevent impacts on equipment efficiency. The second chapter evaluates the quality of boiler feedwater using exploratory methods such as PCA and minimum spanning tree (MST)-based clustering. The analysis of 120 water and steam samples identified patterns and levels of purity, with critical variables including conductivity, SiO₂ content, and pH. These approaches eliminated subjective biases and provided precise information to optimize water management practices in sugarcane biorefineries. The integrated results demonstrate the complementarity of the applied methods, offering a robust foundation for preventive monitoring and cogeneration process optimization. This study contributes to preserving critical equipment, reducing operational costs, and promoting sustainability in industries that use biomass as an energy source.

Este trabalho aborda os desafios relacionados à geração de bioeletricidade em indústrias sucroenergéticas, com foco na formação de incrustações e na gestão da qualidade da água no processo de geração de vapor. Utilizando caldeiras aquatubulares alimentadas por bagaço e palha de cana-de-açúcar, essas biorrefinarias produzem vapor de alta pressão para mover turbinas e gerar energia elétrica, tanto para consumo interno quanto para o sistema elétrico nacional. A tese foi estruturada em dois capítulos. No primeiro, investigou-se a formação de incrustações em turbogeradores, empregando técnicas como fluorescência de raios X (ED-XRF) e análise de componentes principais (PCA). Amostras coletadas em pontos críticos das turbinas e caldeiras revelaram a presença predominante de elementos como silício (Si), enxofre (S), cloro (Cl), potássio (K) e cálcio (Ca), que contribuem para a formação de incrustações. Os resultados destacam a relação direta entre a qualidade da água e as incrustações, reforçando a importância de controles rigorosos no tratamento de água para evitar impactos na eficiência operacional dos equipamentos. No segundo capítulo, avaliou-se a qualidade da água de alimentação das caldeiras utilizando métodos exploratórios, como PCA e agrupamento baseado em árvore mínima de expansão (MST). A análise de 120 amostras de água e vapor identificou padrões e níveis de pureza, com variáveis críticas sendo condutividade, teor de SiO₂ e pH. Essas abordagens eliminaram vieses subjetivos e ofereceram informações precisas para otimizar práticas de gestão da água em biorrefinarias de cana-de-açúcar. Os resultados integrados evidenciam a complementaridade dos métodos aplicados, oferecendo uma base sólida para monitoramento preventivo e otimização do processo de cogeração. Este estudo contribui para a preservação de equipamentos críticos, redução de custos operacionais e promoção da sustentabilidade em indústrias que utilizam biomassa como fonte de energia.
Métodos analíticos avançados para a prevenção de incrustações e garantia da qualidade da água em processos de geração de bioenergia
Keywords: Bioelectricity; Scaling; Chemometrics; Cogeneration; Sustainability; Bioeletricidade; Incrustações; Quimiometria; Cogeração; Sustentabilidade